Preparation of Rearranged Allylic Isocyanates from the Reaction of Allylic Alcohols with 1-Cyano-4-dimethylaminopyridinium Bromide - Baidilov, Daler; Makarova, Mariia; Rycek, Lukas; Hudlicky, Tomas (Synthesis, 2018)
A shorter and less costly alternative to Ichikawa’s [1,3]-transposition protocol for cyanates to isocyanates is described.
Keywords: sigmatropic rearrangement; [1,3]-transposition; allylic alcohol; methodology; total synthesis